An empirical investigation of the dynamic relations between macroeconomic factors and the stock markets of Malaysia and Thailand - Ramin Cooper Maysami,; Sim, Hsein Hui (Penerbit Universiti Kebangsaan Malaysia, 2001)
This paper employs the Error-Correction Modeling technique to examine the relationship between macroeconomics variables and the stock returns of Malaysia and Thailand. The study extends Mukherje and Naka's (1995) analysis of the Japanese Market. In addition, the article expands the results obtained by Maysami and Koh (2000) through the employment of Hendry's (1986) approach which allows a making inferences to the short-run relationship between macroeconomic variables analyzed are interest rate, inflation, money supply, exchange rate and real activity. A dummy variable is included to capture the impact of the 1997 Asian financial crisis. The results confirm the existence of such relationships, but type and magnitude of the associations seem to differ depending on the country's financial structure. The paper presents the economic interpretation for the dependence of the stock indices on these variables as well as discussing the mechanism of the relationship